1987
DOI: 10.1007/bf01310713
|View full text |Cite
|
Sign up to set email alerts
|

Conformational specificity of monoclonal antibodies used in the diagnosis of tomato mosaic virus

Abstract: Ten monoclonal antibodies (McAbs) were raised to the tobamovirus, tomato mosaic virus (ToMV). Seven of the McAbs reacted with ToMV only when tested in an ELISA format, involving antibody-coated plates, which preserved the quaternary conformation of the viral protein. Two McAbs which reacted with ToMV only in an ELISA using virus-coated plates recognized an antigenic determinant present only on the disassembled form of the viral coat protein. One McAb reacted with both the assembled and dissociated forms of ToM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Of the five ELISA procedures using MAbs (procedures 2, 3, 4, 5 and 6; Table 1), procedure 5 was the most appropriate in revealing serological differences between isolates. Because this test requires a MAb on each side of the antigen (one as a coating antibody and one as a detecting antibody), two levels of high specificity in the detection of the virus are introduced (Dekker et al, 1987;Huguenot et al, 1989). Based on preliminary screening, 350 combinations of MAbs were selected for comparison with the 16 isolates using ELISA procedure 5.…”
Section: Resultsmentioning
confidence: 99%
“…Of the five ELISA procedures using MAbs (procedures 2, 3, 4, 5 and 6; Table 1), procedure 5 was the most appropriate in revealing serological differences between isolates. Because this test requires a MAb on each side of the antigen (one as a coating antibody and one as a detecting antibody), two levels of high specificity in the detection of the virus are introduced (Dekker et al, 1987;Huguenot et al, 1989). Based on preliminary screening, 350 combinations of MAbs were selected for comparison with the 16 isolates using ELISA procedure 5.…”
Section: Resultsmentioning
confidence: 99%
“…None of the MAbs showed any cross-reactivity with isolates that differed from M(N)M by an SDI value greater than 4.0. Cross-reactivity studies in the tobamovirus group have shown that MAbs are generally unable to detect an antigenic relationship between two viruses separated by an SDI value of 4.0 (Briand et al, 1982;Dekker et al, 1987). …”
Section: Discussionmentioning
confidence: 99%
“…Having the advantage that already staining pattern in this test may give an indication whether MAbs are directed to outer glycoproteins, the test depends on manual inspection of the plates and is more di cult to standardize; in addition use of formalin may denature sensitive epitopes. To be able to use ELISA technique for high throughput screening, investigators have used antibody-or poly L-lysine-coated plates to capture and thereby preserve the conformation of a viral protein [53,54]. Our test system relied on the lectin properties of ConA as an anchor for the antigen, a system previously shown to preserves conformational epitopes of viral glycoproteins [40,41] By using a genotype 2.VI speci c monoclonal antibody that is highly reactive by HI [55], we could demonstrate, that the ConA-ELISA preserves NDV epitopes sensitive to receptor blocking.…”
Section: Preparation Of Monoclonal Antibodiesmentioning
confidence: 99%